Tumour necrosis factor-α but not lipopolysaccharide enhances preference of murine dendritic cells for Th2 differentiation - Kikuchi, Kazuhiro (Blackwell Science Inc, 2003)
Using murine spleen-derived dendritic cells (DC) and DO11.10 T cells specific for ovalbumin (OVA), the influences of maturational condition and antigen dose on the capability of DC to induce helper T-cell (Th) differentiation were analysed. Immature DC (iDC) with high- or low-dose OVA(323–339) predominantly induced Th1 or Th2 responses in DO11.10 T cells, respectively. DC matured by tumour necrosis factor-α (TNF/DC) induced a significantly higher Th2 response in the presence of low-dose OVA(323–339) than iDC and DC matured by lipopolysaccharide (LPS) (LPS/DC). In the presence of high-dose OVA(323–339), LPS/DC induced significantly lower levels of Th1 response than iDC. Under these conditions no difference in the Th1 response was noted between TNF/DC and iDC. The enhanced capability of TNF/DC with a low-dose antigen for Th2 polarization and the decreased preference of LPS/DC with a high-dose antigen to Th1 polarization were not related to the amount of IL-12 produced in these cultures. These results demonstrate for the first time that TNF/DC with a low-dose antigen are potent inducers of Th2 differentiation.